Outcome of Patients with Mixed Aortic Valve Disease Undergoing Transfemoral Aortic Valve Replacement. Issue 3 (4th July 2017) - Seeger, Julia; Gonska, Birgid; Mörike, Johannes; Rottbauer, Wolfgang; Wöhrle, Jochen
ABSTRACT: Background: Data on transfemoral aortic valve replacement (TAVR) in patients with mixed aortic valve disease (MAVD) compared with aortic stenosis (AS) are missing. The aims of this study were to assess feasibility of TAVR in MAVD and evaluate the impact on short- and long-term outcome. The primary endpoint was all-cause mortality or disabling stroke within 12 months. Methods: Between 2014 and 2016, 734 patients were enrolled (clinicaltrials.gov NCT02162069), 665 had AS, 69 presented with MAVD. Mixed aortic valve disease was defined as coexistence of severe aortic stenosis and moderate to severe aortic regurgitation (AR). Results: VARC-2 early safety endpoint at 30 days was 8.1% in isolated AS and 10.1% in MAVD ( p = 0.57) with no significant differences in all-cause mortality (AS 1.8%, MAVD 4.3%, p = 0.16) and rate of disabling stroke (AS 1.7%, MAVD 1.4%, p = 0.89). There was no difference in residual aortic regurgitation between groups. The primary endpoint at 12 months was comparable (AS 18.3%, MAVD 19.9%, p = 0.87). Within 24 months (AS 26.9%, MAVD 19.9%, p = 0.10) there was no significant difference in all-cause mortality or disabling stroke. Rate of rehospitalization for congestive heart failure did not differ between groups. In multivariate analyses STS for mortality ( p < 0.01) and atrial fibrillation ( p = 0.02) were independent predictors for the primary endpoint at 12 months. In a propensity matched population outcomes were not different within 12 and 24 months. Conclusion: TAVR in patients with MAVD is associated with a comparable 30 days, 12- and 24-month clinical outcome compared to patients undergoing TAVR for aortic stenosis.